STATUS HEMATOLOGIS BROILER UMUR 6 MINGGU YANG DIBERI RANSUM KOMERSIAL DAN PROBIO FMplus - Maria Yanti Duka; Bambang Hadisutanto; Helda . (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2019)
Blood is one of the parameters of the animal health status because blood has a function related to the transportation component in the body as nutrients, oxygen, carbon dioxide, metabolites, hormones, heat, and immune. The additional functions of blood is associated with fluid balance and pH of the body. The aim of this study was to determine the hematologic status of broiler age of 6 weeks were given rations of commercial and PROBIO FMplus. Lactobacillus was given in drinking water to determine the hematologic status broiler among erythrocytes, hemoglobin, hematocrit and leukocytes. This study useds a completely randomized design (CRD). with treatments without the addition of PROBIO FMplus (R0), 5% PROBIO FMplus (R1), 10% PROBIO FMplus (R2), 15% PROBIO FMplus (R3) and 20% PROBIO FMplus (R4) which is repeated 5 times. The results showed that the treatment did not give a significant (P> 0.05) on levels of hemoglobin, hematocrit, erythrocytes and leukocytes. The conclusion is administration of PROBIO FMplus on broiler with different levels of administration that does not give effect to increasing level of hemoglobin, hematocrit, erythrocytes and leukocytes.